142.
а) 3a²b·2ab² = 2·3·a²⁺¹·b¹⁺² = 6a³b³
б) ab² · a² · b³ ·
![\frac{1}{2} \frac{1}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B2%7D+)
ab =
![\frac{1}{2} \frac{1}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B2%7D+)
a¹⁺²⁺¹ b²⁺³⁺¹ =
![\frac{1}{2} \frac{1}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B2%7D+)
a⁴ b⁶
в) ( a³ b⁵ ) : (a² b³) = a³⁻² · b⁵⁻³ = ab²
г)
143.
-(-3)⁹·(-3)⁶ = -(-3)¹⁵ > 0
(-2)⁷ - (-2)⁴·(-2)³ = (-2)⁷ - (-2)⁷ = 0
(-6)¹⁸ : (-6)³ = (-6)¹⁵ < 0
5 + (-5)⁹:(-5)⁸ = 5 + (-5)⁹⁻⁸ = 5 + (-5)¹ = 5 - 5 = 0